Diplomatik Sultan Abdul Hamid di Kerajaan Bima Tahun 1773-1817 M - Kartini Mawaddah (UIN Sumatera Utara Medan, 2017)
Sultan Abdul Hamid was the Bima sultan who ruled for the longest time in the Sultanate of Bima and felt two periods namely, the VOC and the Dutch East Indies. Since the beginning of Islamization and the system of government transformed, Islamic values began to be implanted in government and experienced development. When the Company succeeded in positioning Bima, it was all difficult and declining. The existence of the sultanate began to be threatened because the sultans treated like a doll and much harm the people of Bima. This study examines the diplomacy of the time of Sultan Abdul Hamid Muhammad Syah in Bima in 1773-1817 AD, with the aim of describing the diplomacy form of the sultan in the eastern part of Indonesia, as well as describing the policy in several fields. This research provides information that Sultan Abdul Hamid seeks to create a peaceful atmosphere of the Milky Way without any bloodshed and seeks to meet all the needs of the community through its cooperation with the Company. He created the imperial emblem as a symbol of the power of the Milky Way and the power of Islam in Bima at that time, meaning that all layers of the Bima community must submit to and obey the Law of Hadat and Islamic Law. Through its engagement with the UK, people's incomes have increased from the previous through free trade in the UK. Abdul Hamid is a sultan who has a passion for history and art. He succeeded in collecting historical records now known as Bo 'Sangaji Kai, which contained the social, political, economic and cultural features that were read by later generations.